Analisis Kebangkrutan Pada Perushaan PT Sumber Alfaria Trijaya Tbk. Menggunakan Metode Altman Z-Score Modifikasi (1995) - Diva Rizky Nur Rahmah; Nurlinda (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research analyzes the bankruptcy potential of PT Sumber Alfaria Trijaya Tbk using Altman Z-Score Modification (1995). Focusing on working capital ratio, retained earnings, earnings before interest and taxes, and equity book value, the analysis spans from 2018 to 2022. The results indicate that the company is in the Safe Zone with an average Z-Score of 1.13986, reflecting a robust financial sustainability. However, it is advisable to maintain regular monitoring and analysis.